Absolute total electron impact ionization cross-sections for many-atom organic and halocarbon species. - Bull, J; Harland, P; Vallance, C (2012)
The experimental determination of absolute total electron impact ionization cross-sections for polyatomic molecules has traditionally been a difficult task and restricted to a small range of species. This article reviews the performance of three models to estimate the maximum ionization cross-sections of some 65 polyatomic organic and halocarbon species. Cross-sections for all of the species studied have been measured experimentally using the same instrument, providing a complete data set for comparison with the model predictions. The three models studied are the empirical correlation between maximum ionization cross-section and molecular polarizability, the well-known binary encounter Bethe (BEB) model, and the functional group additivity model. The excellent agreement with experiment found for all three models, provided that calculated electronic structure parameters of suitably high quality are used for the first two, allows the prediction of total electron-impact ionization cross-sections to at least 7% precision for similar molecules that have not been experimentally characterized.